2021
DOI: 10.1186/s12913-021-06188-8
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ views and experiences from setting up a shared patient portal for primary and specialist health services- a qualitative study

Abstract: Background Recently, there has been an increasing focus among healthcare organisations on implementing patient portals. Previous studies have mainly focussed on the experiences of patient portal use. Few have investigated the processes of deciding what content and features to make available, in particular for shared portals across healthcare domains. The aim of the study was to investigate views on content and experiences from the configuration process among participants involved in setting up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…While patient portals continue to be implemented within health systems across North America, the use of these portals for care delivery remains inconsistent, where the level of integration within clinic workflows varies across health organizations and even clinics within a health organization ( 13 ). Additionally, reporting on the impact of portals on patient experience and perception of quality of care is limited and predominately qualitative (ie, interview) data ( 14 ,– 16 ). Moreover, while these platforms have become a key mechanism for supporting the management of the pandemic, there is a lack of evidence and data about the adoption and use of portals over the last 18 months in the Canadian setting.…”
Section: Introductionmentioning
confidence: 99%
“…While patient portals continue to be implemented within health systems across North America, the use of these portals for care delivery remains inconsistent, where the level of integration within clinic workflows varies across health organizations and even clinics within a health organization ( 13 ). Additionally, reporting on the impact of portals on patient experience and perception of quality of care is limited and predominately qualitative (ie, interview) data ( 14 ,– 16 ). Moreover, while these platforms have become a key mechanism for supporting the management of the pandemic, there is a lack of evidence and data about the adoption and use of portals over the last 18 months in the Canadian setting.…”
Section: Introductionmentioning
confidence: 99%
“…Patients, for example, might increasingly use digital interventions as partial surrogates for information and support that they would have otherwise obtained from HCPs, thereby resulting in fewer interactions and weaker mutual bonds with HCPs. Conversely, participation in an OHC or social media platforms or engagement with digital interventions (in general) might trigger patient queries and requests for subsequent contact with HCPs; hence, promotion of online peer support may end up constituting an extra, time-consuming task for HCPs [ 20 , 50 , 51 ]. This is important, bearing in mind the increasing workload of clinicians in the UK primary care setting.…”
Section: Ethicsmentioning
confidence: 99%
“…Some physicians have expressed concerns about using patient portals, including causing distress to patients, misunderstandings and increased physician workloads (Huvila et al , 2021; Nøst et al , 2021). However, some studies have reported that patients understood the health information and found it to be useful (Leveille et al , 2020), while others found that patient portals can reduce patients’ anxiety and stress (Kruse et al , 2015; Nøst et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%